2021
DOI: 10.1021/acs.orglett.1c03720
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Aminomethylative Oppolzer-Type Cyclization of Enynes: Access to Aminomethylated Benzofulvenes

Abstract: A novel palladium-catalyzed Oppolzer-type cyclization reaction aided by the aminomethyl cyclopalladated complex has been developed, which provides rapid access to functionalized benzofulvenes with excellent stereoselectivity. The corresponding products can undergo Diels–Alder reaction with maleimides, providing a series of complex polycyclic compounds with excellent regio- and stereoselectivities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…10 In 2021, Huang demonstrated that the in situ generated aminomethyl cyclopalladated complexes from N , O -acetals could chemoselectively insert into the triple bond of the 1,3-enynes, and the resultant π-allylpalladium species underwent intramolecular Oppolzer-type cyclisation with the pendant alkene moiety to furnish densely functionalised benzofulvenes, but no chiral information was introduced (Scheme 1a). 11 Recently, our group uncovered that chiral Pd(0)/ligand complex could act as an asymmetric π-Lewis base catalyst to enhance the nucleophilicity of 1,3-enynes through η 2 -coordination with the double bond, thus facilitating vinylogous addition to N -sulfonyl imines. Subsequent Suzuki coupling with organoboronic reagents delivered tetrasubstituted alkenes in an exclusive cis -difunctionalisation pattern (Scheme 1b).…”
Section: Introductionmentioning
confidence: 99%
“…10 In 2021, Huang demonstrated that the in situ generated aminomethyl cyclopalladated complexes from N , O -acetals could chemoselectively insert into the triple bond of the 1,3-enynes, and the resultant π-allylpalladium species underwent intramolecular Oppolzer-type cyclisation with the pendant alkene moiety to furnish densely functionalised benzofulvenes, but no chiral information was introduced (Scheme 1a). 11 Recently, our group uncovered that chiral Pd(0)/ligand complex could act as an asymmetric π-Lewis base catalyst to enhance the nucleophilicity of 1,3-enynes through η 2 -coordination with the double bond, thus facilitating vinylogous addition to N -sulfonyl imines. Subsequent Suzuki coupling with organoboronic reagents delivered tetrasubstituted alkenes in an exclusive cis -difunctionalisation pattern (Scheme 1b).…”
Section: Introductionmentioning
confidence: 99%